2007
DOI: 10.1111/j.1365-2222.2007.02700.x
|View full text |Cite
|
Sign up to set email alerts
|

Interference of methysergide, a specific 5‐hydroxytryptamine receptor antagonist, with airway chronic allergic inflammation and remodelling in a murine model of asthma

Abstract: Serotonin may contribute to the development and maintenance of remodelling through the release of cytokines and of fibrogenic mediators. Serotonin should therefore be considered as relevant for the development and maintenance of airway remodelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…We have previously shown that Aspergillus fumigates –induced increases of IgE in airways are associated with eosinophil-dependent AHR24; others have reported an attenuation of allergen-induced increases in IgE by histamine and serotonin antagonists 25,26. Using an IgE passive sensitization model in human small airways to replicate atopic conditions,22,23 the effects of C-027 on IgE passively sensitized induced bronchoconstriction were examined.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that Aspergillus fumigates –induced increases of IgE in airways are associated with eosinophil-dependent AHR24; others have reported an attenuation of allergen-induced increases in IgE by histamine and serotonin antagonists 25,26. Using an IgE passive sensitization model in human small airways to replicate atopic conditions,22,23 the effects of C-027 on IgE passively sensitized induced bronchoconstriction were examined.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report that serotonin is closely linked to inflammatory responses, including the induction of mast cell adhesion and migration, activation of alveolar macrophages, and development and maintenance of arterial remodeling through the release of cytokines [33][34][35] . It is found that fluoxetine has anti-inflammatory properties and that there is a positive correlation between SERT and cytokine mRNA expression in patients with depression, who are affected by chronic treatment with fluoxetine [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Via the 5-HT2A receptor eosinophil recruitment, airway inflammation, airway hyperresponsiveness, and remodeling is mediated in allergic asthma (7981). In 2013, Kang et al showed that serotonin induces eosinophil trafficking and recruitment via activation of ROCK, MAPK, PI3K, and the PKC-calmodulin pathway (78).…”
Section: Serotonin Effects On Immune Cellsmentioning
confidence: 99%